The Potency of Land Management to Minimize the Incidence of Basal Stem Rot (Ganoderma boninense) in The Next Generation of Oil Palm Plantation - Sisko Budianto; Diny Evitasari (Nusantara Science and Technology Proceedings, 2022)
Ganoderma causes basal stem rot disease is a serious threat to the palm oil industry, especially in Malaysia and Indonesia. Field controlling with certain chemicals and biological agents have not been reported to be successful in reducing the Ganoderma incidence. This paper will be reporting about the potency of land management to minimize the incidence of basal stem rot disease in the next generation of oil palm plantations. Three methods of land management during the replanting process have been implemented, those are Windrowing the plant remnants (Windrow 1:1 & Windrow 2:1) as the main plot, Poisoning (No Poisoning and Poisoning) as a sub-plot and Fallowing (planting immediately and fallowing) as a sub-sub plot. The incidence of disease began to be observed two years after planting, by observing the canopy symptoms and the presence of Ganoderma’s fruiting bodies. Observations were made for 20 years, where at 5 years after planting, infections began to appear in the interaction treatment which belonged to windrow 1:1, non-poisoning and planting immediately. Meanwhile, at the end of the observation (20 years after planting), only the fallowing factor had a significant effect on the incidence of disease, where the percentage of disease incidence was half lower than without planting immediately (48.75%: 84.13%). This shows that the farther the plant is from the inoculum source (Windrow 2:1) will prevent the root contact of new plant to plant remnants and leaving the land not to be planted with oil palm for a certain period of time, reduced soil-borne disease agents, especially Ganoderma pathogens. Soil ploughing had been carried out exposing the soil to sunlight and exposing soil-borne disease organisms during the fallow process.